A novel counter‐selection method for markerless genetic modification in Synechocystis sp. PCC 6803. (4th December 2012) - Cheah, Yi Ern; Albers, Stevan C.; Peebles, Christie A. M.
Abstract The cyanobacterium Synechocystis sp. PCC 6803 is a photosynthetic organism capable of efficient harnessing of solar energy while capturing CO2 from the environment. Methods to genetically alter its genomic DNA are essential for elucidating gene functions and are useful tools for metabolic engineering. In this study, a novel counter‐selection method for the genetic alteration of Synechocystis was developed. This method utilizes the nickel inducible expression of mazF, a general protein synthesis inhibitor, as a counter‐selection marker. Counter‐selection is particularly useful because the engineered strain is free of any markers which make further genetic modification independent of available antibiotic resistance genes. The usability of this method was further demonstrated by altering genes at several loci in two variants of Synechocystis. © 2012 American Institute of Chemical Engineers Biotechnol. Prog., 2013